Case Report: Diagnosis and Management of a 28-Year-Old Male Patient with Systemic Contact Dermatitis at Cut Meutia Hospital, North Aceh - Ramdhani, Cepi; Mellaratna, Wizar Putri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Systemic contact dermatitis (SCD) is a skin condition in which a person who is sensitized to an allergen through the skin will react to the same allergen or cross-react through systemic routes, such as oral, intravenous, intramuscular, inhalation, transmucosal, or transcutaneous exposure. A 28-year-old male patient came to the Cut Meutia Hospital Dermatology and Venereology Clinic with complaints of itching accompanied by hyperpigmentation all over the body since the last 3 months. From the anamnesis, physical examination and dermatological examination, the patient was diagnosed with Systemic Contact Dermatitis. Treatment of SCD involves allergen avoidance as determined by clinical history. For difficult cases, immunosuppressive agents can be used to manage SCD in patients who fail topical corticosteroids or dietary avoidance